Fascism - Griffin, Roger 1948- Hrsg (Oxford readers, 1995)
1. The War as a Source of National Renewal / Giovanni Papini -- 2. The War as a Proletarian Cause / Revolutionary Syndicalism -- 3. The War as the Catharsis of Italian Society / Filippo T. Marinetti -- 4. The War as a Revolutionary Event / Benito Mussolini -- 5. 'Trenchocracy' / Benito Mussolini -- 6. The Futurist Vision of the New Italy / Political Futurism -- 7. From the Old Italy to the New / Alfredo Rocco -- 8. The War as the Midwife of a New Italian People / Roberto Parinacci -- 9. San Sepulcro Fascism / Benito Mussolini -- 10. The Regency of Fiume as the Harbinger of the New Italy / Gabriele D'Annunzio and Alceste De Ambris -- 11. The Nationalist Blueprint for a New Italy / The Italian Nationalist Association -- 12. The Squadristi as the Revolutionaries of the New Italy / Mario Piazzesi -- 13. Fascism as the Victory of the New Italy / Luigi Federzoni -- 14. The Incorporation of the Peasantry into the Italian Nation / Benito Mussolini